2020
DOI: 10.1111/jog.14510
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for patients with early‐stage cervical cancer: A study of 374 patients

Abstract: AimThis study aimed to identify the postoperative histological features affecting the prognosis of patients with early‐stage cervical cancer who underwent open radical hysterectomy.MethodsThis retrospective study enrolled 374 patients with pT1a, 1b1 and 2a1 early‐stage cervical cancer who underwent open radical hysterectomy between 2001 and 2018. Survival outcomes were analyzed by Kaplan–Meier method and compared with log‐rank test. Using the Cox proportional hazards regression test, we conducted a multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A principal type of CC is squamous cell carcinoma (SCC), diagnosed in 75%–80% of cases, followed by adenocarcinoma (AC) diagnosed in 20%–25% of cases; adenosquamous cell carcinoma (ASC) is a rare type of CC. Previous studies have reported inconsistent prognoses for these different types of CC, with similar outcomes reported in several studies, 11–21 while others have reported differences in prognosis 22–29 . In addition, various histological types of CC respond differently to initial treatment, which has an impact on prognosis 28,30–33 .…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…A principal type of CC is squamous cell carcinoma (SCC), diagnosed in 75%–80% of cases, followed by adenocarcinoma (AC) diagnosed in 20%–25% of cases; adenosquamous cell carcinoma (ASC) is a rare type of CC. Previous studies have reported inconsistent prognoses for these different types of CC, with similar outcomes reported in several studies, 11–21 while others have reported differences in prognosis 22–29 . In addition, various histological types of CC respond differently to initial treatment, which has an impact on prognosis 28,30–33 .…”
Section: Introductionmentioning
confidence: 67%
“…Previous studies have reported comparable prognoses of SCC and AC/ASC types of CC, 11–21 as well as for AC and ASC 21 . Recently, differences in oncological characteristics, including pathophysiology, epidemiology, patterns of tumor metastasis, and prognosis, have been reported between the different histological types of CC 22–29 . The presence or absence of LNM might influence the outcomes, with comparable prognoses for SCC and AC types of CC without LNM but with a worse prognosis for AC than SCC type with LNM 37,38 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Some previous studies also showed that neurodegenerative disease spurs on cervical and ovarian cancer [ 9 , 10 ]. National Cancer Institute summarizes that cervical tumor constitutes in the cervix, a body part associating with uterus and vagina [ 11 , 12 ] Human Papillomavirus (HPV) is the main reason behind cervical cancer [ 13 ] For the well-known impact of HPV on cervical cancer, an examination [ 14 ] was made which audits the articles based on the information on HPV and cervical cancer among Malaysian inhabitants before and after the usage of HPV antibody programs. In [ 15 ] a research has been conveyed a study where he found cervical slowly develops without showing any indication at the beginning seemingly hard to discover but can be noticed with respective pap tests.…”
Section: Introductionmentioning
confidence: 99%